Tawḥīdī Epistemology: Uniting Rationality, Empiricism, and Transcendence within the Framework of Islamic Science - Romdlony, Muhammad Zakiyullah; Darmawan, Dadang; Anwar, Rosihon; Rahman, Mohammad Taufiq (International Journal of Nusantara Islam, 2025)
This article proposes an integrative epistemology model based on tawḥīd (Tawḥīdī Epistemology) that synthesizes three main frameworks: Burhān al-Ṣiddīqīn (Ibn Sina's ontological argument about Wājib al-Wujūd); the Scientific Method (logico-hypothetico-verification), and the Revelation Guides Science paradigm from UIN Sunan Gunung Djati Bandung. Through philosophical analysis and multidisciplinary case studies, this research demonstrates that this integration not only overcomes the science-religion dichotomy but also offers a structured methodology for dual validation (empirical and normative). This article enriches the discourse of contemporary Islamic philosophy by actualizing Ibn Sina's legacy in the context of modern science, while also addressing postmodern critiques of the objectivity of science.